2019
DOI: 10.1002/hed.26036
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PD‐L1 expression and human papillomavirus status in anti‐PD1/PDL1 immunotherapy for head and neck squamous cell carcinoma—Systematic review and meta‐analysis

Abstract: Programmed cell death‐1 (PD‐1) pathway inhibition in head and neck squamous cell carcinoma (HNSCC) has demonstrated inconsistent efficacy regarding human papillomavirus (HPV) status and PD‐L1 expression. This study compared outcomes in HNSCC in the context of PD‐L1 and HPV expression. Outcomes: PD‐L1 and HPV expression; overall survival (OS), and tumor response (ORR). 1088 patients received PD‐1/L1 inhibitors. Four methodologies were identified in determining PD‐L1 expression, most commonly using the Dako PD‐L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 53 publications
2
53
1
Order By: Relevance
“…The meta-analysis of the outcomes seems to confirm that higher rates of PD-L1 expression enhance the overall response rate (ORR) of these patients: 18.9% for expressers versus 8.8% for non-expressers. On the other hand, in contrast to previous suggestions, no differences were observed in survival or tumor response among the HPV positive patients [ 109 ].…”
Section: Msi and Immunotherapy Of Hnccontrasting
confidence: 93%
“…The meta-analysis of the outcomes seems to confirm that higher rates of PD-L1 expression enhance the overall response rate (ORR) of these patients: 18.9% for expressers versus 8.8% for non-expressers. On the other hand, in contrast to previous suggestions, no differences were observed in survival or tumor response among the HPV positive patients [ 109 ].…”
Section: Msi and Immunotherapy Of Hnccontrasting
confidence: 93%
“…12,39,40 A recent systematic review highlighted that HNSCC tumors with PD-L1 expression show a greater tumor response and better overall survival. 41 Besides the approval of PD1/PD-L1 inhibitors for many invasive cancer types, the role of the PD1/PD-L1 axis has also been investigated in precancerous lesions, particularly in intraepithelial neoplasia of the cervix and in breast DCIS. [8][9][10][11] Given the role of the PD1/PD-L1 axis in the development of immune tolerance against tumorassociated antigens and the complexity of interactions in the TME, it has been speculated that intraepithelial neoplasia and precancerous lesions could reflect a situation where there is a balance between the host immune response to cancer development and the cancer's ability to escape the host response.…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy with PD1/PD‐L1 inhibitors has been approved in the last few years for advanced HNSCC 12,39,40 . A recent systematic review highlighted that HNSCC tumors with PD‐L1 expression show a greater tumor response and better overall survival 41 . Besides the approval of PD1/PD‐L1 inhibitors for many invasive cancer types, the role of the PD1/PD‐L1 axis has also been investigated in precancerous lesions, particularly in intraepithelial neoplasia of the cervix and in breast DCIS 8‐11 .…”
Section: Discussionmentioning
confidence: 99%
“…Given the biologic differences, questions have arisen as to whether immunotherapy efficacy is affected by HPV status. A systematic review of clinical trials using immunotherapy in HNSCC found no significant difference in ORR, stable disease, progressive disease, or OS when the results were stratified by HPV status 65 . As a whole, immunotherapy has proven to be effective for both HPV‐related and HPV‐unrelated HNSCC; therefore, as of the publication of this article, HPV status should not play a role in the decision to use these agents in clinical practice.…”
Section: Head and Neck Cancermentioning
confidence: 95%
“…A systematic review of clinical trials using immunotherapy in HNSCC found no significant difference in ORR, stable disease, progressive disease, or OS when the results were stratified by HPV status. 65 As a whole, immunotherapy has proven to be effective for both HPVrelated and HPV-unrelated HNSCC; therefore, as of the publication of this article, HPV status should not play a role in the decision to use these agents in clinical practice. Research focusing on the targeting of HPV-related HNSCC is eagerly awaited given its implications on the field of immunotherapy in virally mediated tumors.…”
Section: Head and Neck Cancermentioning
confidence: 99%